THE IMPORTANCE OF TOURISM IN PRESENT DAY - Teshaboyeva, Nafisa (Журнал иностранных языков и лингвистики, 2023)
The article deals with the tourism sector is one of the largest money-generating sectors in the world. It is an ever-developing industry, where new niches seem to crop up every now and then. Moreover, tourism development strategy as a tool for economic growth, and in particular, identifying those that need a strategy, can lead to the product development and marketing strategies, profitability improvement, investment attraction, the role of government and business section in determining the quality and quantity of the needed resources, and supporting the regional plans.